The Bionomic Equilibrium Model for Balancing Forest Conservation and Economic Growth: Empirical Evidence from Indonesia: - Jamal, Sri Wahyuni; Suparno, Suparno; Hadiyanti, Sofia Ulfa Eka; Sadidah, Dian; Dewi, Mutiara (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2023)
Abstract: The objective of this study is to balance forest conservation with economic growth while accounting for the rate of deforestation. The methodology employed in this research utilizes a mathematical modeling approach, specifically adopting the logistic model to represent forest growth rates. In addition, numerical analysis is applied to illustrate the impact of economic activities on forest areas. The data used in the study consist of deforestation rates in Indonesia from 2000 to 2021. The findings indicate that the rate of economic activity in forested areas is directly proportional to the reduction in forest area. If the rate of deforestation due to economic activity approaches the forest growth rate, the likelihood of forest area reduction increases, and forest depletion will occur if the two rates become equal. To resolve the dilemma between forest conservation and economic growth, this study proposes a solution consisting of three key steps: (1) establishing a minimum forest area that is strictly protected from economic exploitation; (2) setting the ratio between forest growth rates and economic activity rates as a primary foundation for ensuring sustainable forest conservation and economic development; and (3) calculating environmental costs, such as reforestation, based on the proportional relationship between deforestation rates and forest growth rates. Keywords: Deforestation, Environmental Cost, Economy, Forest, Growth Rate